Homeopathic Ear Drops as an Adjunct in Reducing Antibiotic Usage in Children With Acute Otitis Media - James A. Taylor MD; Jennifer Jacobs MD, MPH (SAGE Publishing, 2014)
Objective . To determine if use of a homeopathic ear drop preparation reduces antibiotic use in children diagnosed with acute otitis media (AOM). Methods . Children 6 months to 11 years old, diagnosed with AOM and managed with a delayed antibiotic approach, were randomized to standard therapy alone or standard therapy plus a homeopathic ear drop preparation. The primary outcome was whether or not the antibiotic prescription given at the index visit was filled during a 12- to 15-day follow-up period. Results . Among 210 enrolled children, follow-up antibiotic data were collected on 206. During the 12- to 15-day follow-up period, fewer parents of children randomized to the homeopathic ear drops group filled the antibiotic prescription compared with those of children receiving standard therapy alone (26.9% and 41.2%, respectively, P = .032). Conclusion . Homeopathic ear drops may be effective in reducing the use of antibiotics in children with AOM managed with a delayed antibiotic approach.